2014
DOI: 10.1007/s00392-014-0705-3
|View full text |Cite
|
Sign up to set email alerts
|

Characteristic of c-Kit+ progenitor cells in explanted human hearts

Abstract: According to literature data, self-renewing, multipotent, and clonogenic cardiac c-Kit+ progenitor cells occur within human myocardium. The aim of this study was to isolate and characterize c-Kit+ progenitor cells from explanted human hearts. Experimental material was obtained from 19 adult and 7 pediatric patients. Successful isolation and culture was achieved for 95 samples (84.1 %) derived from five different regions of the heart: right and left ventricles, atrium, intraventricular septum, and apex. The ave… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 26 publications
3
17
0
Order By: Relevance
“…In the aggregate, these data, detailed below, support the concept that c-kit pos cardiac cells likely represent intermediate phenotypes from more than one progenitor compartment within embryonic cardiomyogenesis, and that c-kit expression, in itself, does not define one specific cardiac precursor. Indeed, c-kit expression has been found in intermediate phenotypes in very early bipotential myogenic FHF progenitors 16 as well as in epicardium-derived cells that undergo EMT to largely make vascular and advential lineages 35, 37, 38, 49, 51, 53, 55, 64-68 . The same may be true of c-kit pos cells isolated from endocardial biopsies 25, 39 (this will be discussed later).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the aggregate, these data, detailed below, support the concept that c-kit pos cardiac cells likely represent intermediate phenotypes from more than one progenitor compartment within embryonic cardiomyogenesis, and that c-kit expression, in itself, does not define one specific cardiac precursor. Indeed, c-kit expression has been found in intermediate phenotypes in very early bipotential myogenic FHF progenitors 16 as well as in epicardium-derived cells that undergo EMT to largely make vascular and advential lineages 35, 37, 38, 49, 51, 53, 55, 64-68 . The same may be true of c-kit pos cells isolated from endocardial biopsies 25, 39 (this will be discussed later).…”
Section: Introductionmentioning
confidence: 99%
“…Many studies by independent groups have consistently shown that adult human c-kit pos cardiac cells express CD105, CD29, and other mesenchymal-associated markers both in vivo and in vitro 11, 51, 65-68, 72-79 . The in vivo expression, assessed by immunohistochemical staining, indicates that this mesenchymal phenotype is inherent to c-kit pos cardiac cells from adult humans and mice and is not the result of in vitro artifacts or culture drift 72 .…”
Section: Introductionmentioning
confidence: 99%
“…Genetic fate-mapping studies showed that endogenous cardiac c-kit POS cells contributed minimally to myocytes; instead, they differentiated into endothelium or mesenchyma (48). Moreover, c-kit–sorted cardiac cells also express mesenchymal markers, and some studies showed that these cells have properties similar to bone marrow mesenchymal cells, with ability to differentiate into bone, cartilage, and adipose cells (10,13,18,19,21,22). Thus, considerable evidence suggests that c-kit POS cardiac cells might be a population of CMCs (3).…”
Section: Discussionmentioning
confidence: 99%
“…The adult mammalian heart contains a distinct population of self-renewing, multipotent cardiac progenitor cells (CPCs) that can partially differentiate into cells with endothelial, cardiac, and smooth muscle cell characteristics [1][2][3][4]. Although it is unclear whether [5] or not [6] these cells are sufficient or necessary for spontaneous regeneration of the heart after injury, several laboratories have shown that transplantation of CPCs improves myocardial recovery and function after infarction [7][8][9][10][11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%